Electrochemical Behavior of Chlorine on Platinum Microdisk and Screen-Printed Electrodes in a Room Temperature Ionic Liquid - Murugappan, Krishnan; Arrigan, Damien; Silvester, Debbie (2015)
As a result of the toxic and corrosive nature of chlorine gas, simple methods for its detection are required for monitoring and control purposes. In this paper, the electrochemical behavior of chlorine on platinum working electrodes in the room temperature ionic liquid (RTIL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][NTf2]) is reported, as a basis for simple sensor devices. Cyclic voltammetry (CV) and chronoamperometry (CA) on a Pt microelectrode revealed the two-electron reduction of Cl2 to chloride ions. On the CV reverse sweep, an oxidation peak due to the oxidation of chloride was observed. The reduction process was diffusion controlled at the concentrations studied (≤4.5% in the gas phase), in contrast to a previous report (J. Phys. Chem. C2008, 112, 19477), which examined only 100% chlorine. The diffusion-controlled currents were linear with gas-phase concentration. Fitting of the CA transients to the Shoup and Szabo expression gave a diffusion coefficient for chlorine in the RTIL of ca. 2.6 × 10–10 m2 s–1. Furthermore, determination of the equilibrium concentration of Cl2 in the RTIL phase as a function of gas-phase concentration enabled a value of 35 to be determined for the Henry’s law dimensionless volatility constant. The electrochemical behavior of chlorine on a Pt screen-printed electrode was also investigated, suggesting that these devices may be useful for chlorine detection in conjunction with suitable RTILs.